Davet ve Tebliğde Üsve-i Hasene Olarak Hz. İbrahim - Efe, Mustafa (My University, 2024)
Kur'an'da Müslümanların, insanlara iyilik yapmalarını emretmeleri ve kötülük yapmaktan sakındırmaları hususunda davet ve tebliğ emredilmektedir. Biz de, bu araştırmada İslam'ın en öncelikli meselelerinden biri olan İslam'a davet ve tebliğin metotları nedir, nasıl bir usulle yapılmalıdır? İslam'a davet edenlerin vasıfları neler olmalıdır? Sorularına Hz. İbrahim özelinde cevap aradık. Ayet-i Kerimelerde insanlara üsve-i hasene (en mükemmel model şahsiyet) olarak gösterilen, müterekkep vasıfları ve görevleri İslam'a davet olan tüm peygamberlerin hayatlarını inceledik. Bilhassa İbrahim'in İslam'a davet ederken takip ettiği usul ve metotları Kur'an ve sünnet merkezli bir bakışla araştırdık.

Invitation and rescript are two important points of Islam. In Quran avoidance of bad habits and good will are commanded. First invitation has started with the first human Adam the Prophet, because as a being human is tempted to forget and leave the path. The mutual goal of all prophets is invitation to Islam. In this work, we explore the methods of invitation to Islam, in which ways it should be made and the qualities a person must possess in order to propagate Islam and we analyzed the verses from Quran regarding the prophets who are presented as best examples to humans. Furthermore, we specifically studied the invitation methods of Hz. Abraham the Prophet with a Quran centered point of view.
Hz. Abraham the Prophet as the Best Example ("Üsve-i Hasene") in Rescript
Keywords: Davet; Tebliğ; İbrâhim Peygamber; Üsve-i Hasene; Peygamberler; Kuran; Hadis; Rescript; Invitation; Epistle; Quran; Abraham Prophets; Good Example